Self-Esteem dan Job Insecurity pada Karyawan Outsourcing - Pande Ketut Bagus Pancadana; P. Henrietta Puji Dwi Astuti Dian Sabatti (Fakultas Psikologi Universitas Sanata Dharma, 2022)
This research focused on examining the relationship between self-esteem and job insecurity in outsourcing employees. The hypothesis of this research was the existence of a negative and significant relationship between self-esteem and job insecurity. There were 211 participants in this study, who were outsourcing employees. Data was collected by using Rosenberg Self-Esteem Scale (RSES, α = 0.745) and Job Insecurity Scale (JIS, α = 0.723). Technique that was used to analyse the data was Spearman's rho correlation technique because the data was not normal. The results showed that there were a negative and significant relationship between self-esteem and job insecurity (r = -0,246; p = 0,000), positive self-esteem and job insecurity (r = -0,237; p = 0,000), negative self-esteem and job insecurity (r = -0,169; p = 0,007). The higher the self-esteem, the lower the job insecurity of outsourcing employees. Keywords: Self-Esteem, Job Insecurity, Outsourcing Employees